Equine hyperadrenocorticism: A report of 4 natural cases - KOUTINAS (X.K. ΚΟΥΤΙΝΑΣ), C. K.; SARIDOMICHELAKIS (Μ.Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ), M. N.; MYLONAKIS (Μ.Ε. ΜΥΛΩΝΑΚΗΣ), M. E.; HAMHOUGIAS (Κ. ΧΑΜΧΟΥΓΙΑΣ), K.; FYTIANOU (Α. ΦΥΤΙΑΝΟΥ), A.; DIAKAKIS (Ν. ΔΙΑΚΑΚΗΣ), N.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F. (Journal of the Hellenic Veterinary Medical Society, 2017)
Hyperadrenocorticism, the most common equine endocrinopathy, is the result of hyperplasia or a functional adenoma of the pars intermedia (intermediate lobe) of the pituitary gland. The study population included a 20-year old Irish hunting gelding (case 1), a 13-year old English Thoroughbred stud horse (case 2), an 18-year old intact male donkey (case 3) and a 22-year old mare belonging to a mixed breed (case 4). From a historical and clinical standpoint, the most common clinical signs were hypertrichosis (4/4), progressive loss of body weight (3/4), polyuria-polydipsia (3/4), laminitis (3/4), depression-lethargy (2/4), sway-back (lordosis) (2/4), pot-belly (2/4), bulging of the supraorbital region due to the excessive deposition of adipose tissue (2/4), hyperhidrosis (2/4) and delayed wound healing (2/4). The results of the routine laboratory testing showed lymphopenia (4/4), anemia (2/4), mature neutrophilia (1/4), monocytosis (1/4), hypertriglyceridemia (4/4), increased ALP activity (3/4), hypocalcemia (3/4) and hypoalbuminemia (2/4). Also, case 2 developed type III diabetes mellitus as a consequence of the disease. The diagnosis of hyperadrenocorticism, that was initially based on the classical clinical signs, noticed in all 4 animals, was further confirmed in 3 of them (cases 1, 3, 4) with the overnight dexamethasone suppression test. Oral bromocryptine (dopamine agonist), that was subsequently prescribed in two horses (cases 1, 4) resulted in a remarkable clinical improvement, first noticed in both animals approximately two months after the beginning of the treatment.